2018
DOI: 10.1177/2397847318801758
|View full text |Cite
|
Sign up to set email alerts
|

Improving the ACGIH threshold limit value (TLV) process

Abstract: The intent of this manuscript is to elucidate needed improvements in American Conference of Governmental Industrial Hygienists (ACGIH) threshold limit value (TLV) deliberations. More broadly, irreproducibility and bias adversely impact the collection, interpretation, statistical analysis, presentation, and reporting of results in many fields. In 2012, Begley and Ellis reported that scientists at Amgen had attempted to confirm published findings related to research topics of possible interest to Amgen. Fifty-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Recently, we addressed the lack of transparency in the ACGIH TLV process. 14 The current analysis extends the previous study by examining every TLV set during the 10-year interval between 2008 and 2018.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Recently, we addressed the lack of transparency in the ACGIH TLV process. 14 The current analysis extends the previous study by examining every TLV set during the 10-year interval between 2008 and 2018.…”
Section: Introductionmentioning
confidence: 53%
“…Compounding the already extremely problematic situation, many studies conducted over the last several years have demonstrated that a large but not exactly determinable percentage of the results in the peer-reviewed academic literature are not reproducible in another laboratory attempting to employ the original protocol. 14 Based on analyses conducted in different fields of study, a reasonable estimate would be that about 40-50% of the biomedical literature is not replicable. 14,[44][45][46][47][48] ACGIH states that the primary resource upon which it relies in setting TLVs is this same body of peer-reviewed academic literature in the midst of a replicability crisis.…”
Section: Recommendations For Improving the Tlv-setting Processmentioning
confidence: 99%
See 3 more Smart Citations